2000
DOI: 10.1177/03635465000280041101
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of High School Wrestling Injuries

Abstract: We performed a prospective study to evaluate injury patterns in a large population of high school wrestlers during one season. Preseason screening was performed on 458 male wrestlers from 14 different high schools. Certified athletic trainers submitted detailed weekly team and individual injury reports. There were 219 injuries in 418 wrestlers followed throughout the season for an overall injury incidence of 52 injuries per 100 wrestlers per season and an injury rate of 6.0 injuries per 1,000 exposures. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
135
3
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(145 citation statements)
references
References 27 publications
5
135
3
2
Order By: Relevance
“…The difficulty in the comparison of data among studies is due to the absence of an uniform standard in the classification of lesion types. 4 The types of lesion most frequently reported in our study were sprains (34.5%) and muscle lesions (30.4%), which is in line with the results presented by Jarrett et al 4 , Pasque et al 5 and Snook 6 . These authors said that contusions are the third most common lesion in wrestlers, unlike our data in which contusions were the least frequent lesions.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The difficulty in the comparison of data among studies is due to the absence of an uniform standard in the classification of lesion types. 4 The types of lesion most frequently reported in our study were sprains (34.5%) and muscle lesions (30.4%), which is in line with the results presented by Jarrett et al 4 , Pasque et al 5 and Snook 6 . These authors said that contusions are the third most common lesion in wrestlers, unlike our data in which contusions were the least frequent lesions.…”
Section: Discussionsupporting
confidence: 92%
“…This time was considerably longer than that encountered by other authors. 1,4,5 This may be a result of the design of our study, in which injuries of lesser severity with shorter length of absence were probably not reported due to a known effect such as memory bias. Knowledge of the more frequent musculoskeletal injuries in wrestlers can help professionals involved in the sport in the preparation of preventive actions and of training programs with the intention of reducing their incidence and of improving the performance of sportsmen and sportswomen.…”
Section: Lower Limbs Upper Limbs Trunkmentioning
confidence: 93%
See 2 more Smart Citations
“…30 For example, Decoster et al 6 found that the rate of ankle injuries was 26% higher in athletes with generalized joint hypermobility than in athletes with normal joint mobility. The demands placed on the joints of an athlete with joint hypermobility are important to consider prospectively, because the joints generally may tolerate repetitive activity better than tasks requiring stabilization.…”
Section: Discussionmentioning
confidence: 99%